Active dielectric metasurface based on phase‐change medium (Laser Photonics Rev. 10(6)/2016). Issue 6 (November 2016) - Chu, Cheng Hung; Tseng, Ming Lun; Chen, Jie; Wu, Pin Chieh; Chen, Yi‐Hao; Wang, Hsiang‐Chu; Chen, Ting‐Yu; Hsieh, Wen Ting; Wu, Hui Jun; Sun, Greg; Tsai, Din Ping
Abstract : Highly tunable dielectric metasurfaces based on subwavelength thick silicon nano‐posts encapsulated in a thin elastic polymer are demonstrated. The proposed platform simultaneously provides a high tuning range, high efficiency, polarization independence, and diffraction limited performance. This platform is highly versatile for developing ultra‐slim and tunable optical devices with widespread applications ranging from stringent packaging consumer electronics to medical devices. (Picture: Cheng Hung Chu et al., 10.1002/lpor.201600106 pp. 986–994, in this issue)